THE SIMILARITIES AND DIFFERENCES OF HANG TUAH AND CINDUA MATO CHARACTERS - Suhardi, Suhardi; Thahirah, Thahirah (Jurnal Pendidikan Bahasa dan Sastra, 2020)
The Malay and Minangkabau people are those who like to speech and act on literature. This can be seen through the existence of several genres of literary works from those ethnic, ranging from the form of saga, tale, and legend. Among them are Hang Tuah and Cindua Mato saga. Hang Tuah saga grew and developed in Malay society, while Cindua Mato saga grew and developed in Minangkabau society. Both sagasare interesting to be studied as an analytical study. First, Hang Tuah and Cindua Mato saga is a great literary work owned by both ethnic groups. As a masterpiece, they both have an appeal to be analyzed in many ways. Secondly, Hang Tuah and Cindua Mato figures by both ethnic communities have become a big myth. Hang Tuah became myth by the Malay community as a brave and loyal figure to the king. So did with the figure of Cindua Mato who became myth by Minangkabau society as a brave and loyal figure to the king. As with other literary works, Hang Tuah and Cindua Mato saga contains the aesthetic, moral, and cultural elements of their owners. It is as stated by Taum that oral literature has an aesthetic effect and moral context as well as a particular society culture. This research analyzed and examined the cultural similarities and differences (characters) in Hang Tuah and Cindua Mato saga. This study is expected to produce the same perception of both sagas. Likewise, the possibility of a kinship element exists between ethnic Malay and Minangkabau.